Genetic determinants of acquired cholestasis: A systems biology approach - Sookoian, Silvia Cristina (2012)
Cholestatic liver diseases encompass a complex spectrum of intrahepatic and cholangiocellular cholestasis, whose etiologies include genetic and environmental components. This review focuses on the role of the genetic component of three adult cholestatic diseases, namely, primary sclerosing cholangitis (PSC), primary biliary cirrhosis (PBC), and intrahepatic cholestasis of pregnancy (ICP). In particular, we integrate genomic, molecular, and physiological data to understand the putative interplay between the underlying genetic mechanisms involved in the susceptibility of these diseases. This approach is based on the hypothesis that a more integrative knowledge of the genetic determinants of cholestatic diseases may have a strong impact on the development of improved therapies. We also propose the strategy of gene prioritization to identity potential candidate genes for disease susceptibility, and show some examples of "leading genes of human cholestatic pathways". Finally, based on the hypothesis that common physiologic processes and molecular networks may influence the risk of adult cholestatic diseases, we used a candidate gene prioritization application based on the use of a protein-protein interaction network as part of the 'interactome'.